The Effect of Passive Ultrasonic Irrigation and XP-Endo Finisher on Post-operative Pain after Endodontic Retreatment on Patients (Randomized Controlled Clinical Trial) - Ashraf, Ahmed; Hussein, Wael; Hashem, Ahmed; Soliman, Amgad (Open Access Macedonian Journal of Medical Sciences, 2022)
AIM: To evaluate the effect of passive ultrasonic irrigation or XP-Endo Finisher on postoperative pain in patients with underextended filling in previously endodontically treated mandibular first molar teeth requiring endodontic retreatment using visual analog scale (VAS) scale at 6, 12, 24, 48, 72 h, and 7 daytime intervals. METHODS: Seventy-eight patients with mandibular first molars which need endodontic retreatment were randomly allocated into one of three separate groups (n = 26); NaviTip group (control), XP-Endo Finisher group, or Ultra X group. Data were statistically analyzed with a significance level of p ≤ 0.05. RESULTS: XP-Endo Finisher agitation and ultrasonic agitation as a final irrigation protocol showed significantly lower pain values than the control group, but there was no significant difference in pain values between the experimental groups. CONCLUSION: Within the limitation of this study, it can be concluded that agitation techniques used during endodontic retreatment decreased the incidence and intensity of post-operative pain.